The truth about the music business a grassroots business and legal guide - Moore, Steve 1962- (Gale virtual reference library, 2005)
Designed for aspiring or current employees in the music business who wish to learn more about the business and legal aspects of their trade. It covers pertinent business and legal information for many professional music careers, from artists, writers, and booking agents to studio managers and major label executives.